Surgical Treatment for Severe Fixed Hyperkyphosis in an Adult Patient Suffering From Ankylosing Spondylitis and Hereditary Hypophosphatemia With Vertebral Osteopetrosis. Issue 8 (October 2020) - Wolfram, Julia M.; Zitt, Emanuel; Bach, Christian M.
Abstract : Purpose: Ankylosing spondylitis and hereditary hypophosphatemia with long-term high dose supplementation of phosphorous and calcitriol can both lead to severe structural abnormalities of the vertebrae. Impairment of spinal mobility and spinal deformity may ultimately necessitate surgical treatment. A severe fixed hyperkyphosis in a patient with ankylosing spondylitis is a surgically demanding condition, therefore, the indication for surgical treatment should be thoroughly considered and chosen individually. Methods: This is an uncommon case with a combination of a severe fixed hyperkyphosis with a Cobb-angle of 105 degrees between Th2 and L4 in an adult male patient suffering from ankylosing spondylitis and X-linked hypophosphatemia with surprisingly massive osteopetrosis. In this paper, the coexisting conditions of late-stage ankylosing spondylitis and long-term treated hereditary hypophosphatemia are highlighted. The surgical treatment with different techniques, complications, and results are well explained. Results: A normal gait and stand were achieved by a long posterior fusion with 3 pedicle subtraction osteotomies on L1, L3, and L5. The surgical correction was performed in 3 stages. Postoperative the patient was administered to a rehabilitation center for 3 months. The hyperkyphosis, the C7 plumbline, and the pelvic retroversion were corrected. Conclusions: Surgical treatment of a severe fixed hyperkyphosis due to ankylosing spondylitis is technically demanding but can be successfully achieved if all surgical challenges and comorbidities are adequately addressed including intraoperative surprising findings like osteopetrotic bone in a patient with hereditary hypophosphatemia as in our case. Abstract : Supplemental Digital Content is available in the text.